Fabrication of Methylammonium Bismuth Iodide Layers Employing Methylamine Vapor Exposure. Issue 18 (17th July 2019) - Stümmler, Dominik; Sanders, Simon; Mühlenbruch, Sebastian; Pfeiffer, Pascal; Simkus, Gintautas; Heuken, Michael; Vescan, Andrei; Kalisch, Holger
Abstract : Methylammonium bismuth iodide (MBI) is a promising candidate for nontoxic perovskite solar cells because of its pronounced stability compared with other lead‐free compounds. Herein, the transformation of solution‐processed BiI3 to MBI employing an exposure to methylamine (MA) vapor is demonstrated. The MA process features a very fast reaction, short process times, and atmospheric‐pressure conditions. The reaction of BiI3 with MA is analyzed and discussed in detail, and the formation of MBI is confirmed via X‐ray diffraction (XRD). Devices based on MA‐treated solution‐deposited BiI3 show performance figures comparable to those of conventionally solution‐processed cells. In conclusion, the results of this study demonstrate that exposure to MA is a promising route toward a fast, versatile, and resource‐efficient production of MA cation based perovskites for solar cell modules. Abstract : In this study, the transformation of solution‐processed BiI3 to methylammonium bismuth iodide employing an exposure to methylamine (MA) vapor is demonstrated. Devices based on MA‐treated solution‐deposited BiI3 show performance figures comparable to those of solution‐processed cells. In conclusion, this study demonstrates that exposure to MA is a promising route toward a fast and versatile production of MA cation based perovskites.